2016
DOI: 10.5897/ajb2016.15386
|View full text |Cite
|
Sign up to set email alerts
|

Organic and conventional vegetables: Comparison of the physical and chemical characteristics and antioxidant activity

Abstract: The objective of this research was to compare the physical and chemical characteristics and antioxidant activity of organic and conventional carrot (Daucus carota), green pepper (Capsicum annuum) and lettuce (Lactuca sativa). Five representative samples of conventional vegetables, certified organic and non-certified organic vegetables were gotten from farms and supermarkets in the city of Rio de Janeiro. The result shows that the organic carrot showed higher acidity (0.11 g % citric acid) and total sugar (5.68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Chard and purslane obtained conventionally showed the lowest antioxidant power. All data obtained agree with the studies carried out by De Oliveira et al (2016), who found that organic crops contain higher amounts of phenolic compounds and higher antioxidant capacity than conventional crops. Interestingly, the content if soluble solids of a given group correlates with the antioxidant capacity, possibly because of water soluble antioxidants like vitamin C (Thaipong et al, 2006).…”
Section: Resultssupporting
confidence: 90%
“…Chard and purslane obtained conventionally showed the lowest antioxidant power. All data obtained agree with the studies carried out by De Oliveira et al (2016), who found that organic crops contain higher amounts of phenolic compounds and higher antioxidant capacity than conventional crops. Interestingly, the content if soluble solids of a given group correlates with the antioxidant capacity, possibly because of water soluble antioxidants like vitamin C (Thaipong et al, 2006).…”
Section: Resultssupporting
confidence: 90%
“…Some earlier studies have similarly found that the production method did not affect the total sugar content in carrots [48,49,64]. However, several studies have concluded that organic vegetables, including carrots, contain more sugars than conventional ones [58,[65][66][67][68]. Total sugar content in carrots could be affected more by climate-related factors than by management methods [69].…”
Section: Discussionmentioning
confidence: 99%
“…The potential toxic effects on human health are associated with pesticide overuse in conventional production systems. If technical recommendations are not adequately followed, the conventional system can be detrimental to human health and contribute to environmental pollution (Fernanda et al, 2016). An alternative to conventionally grown carrots is the organic system, even though it is often considered more expensive.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to conventionally grown carrots is the organic system, even though it is often considered more expensive. Some studies indicate that crops grown in organic production systems have higher levels of protective substances, such as polyphenols, flavonoids, phenols, and antioxidants in general (Castro et al, 2014;Fernanda et al, 2016).…”
Section: Introductionmentioning
confidence: 99%